Liver cancer: etiological factors - Rigail Arosemena , Francisco; Miranda Vargas, Freedy (Revista Universidad de Guayaquil, 1988)
It is one of the most frequent in the world, given that there are countries with a huge incidence: in China and Africa it ranges from 25 to 150 cases per 100,000 inhabitants, while in Latin America it is 7 per 100,000. It is known that the majority Of cases of hepatoma are associated with cirrhosis or chronic hepatitis and, in general, with previous liver disease and also with nodular transformation of the liver. The common precursor in all these cases appears to be hepatocellular dysplasia. In the US, 5% of post-alcoholic cirrhosis develop hepatomas, and 50% of patients with hepatoma are cirrhotic.